Primary bile acids as potential biomarkers for the clinical grading of intrahepatic cholestasis of pregnancy. Issue 1 (4th April 2013) - Chen, Jianbo; Deng, Wenping; Wang, Junwei; Shao, Yong; Ou, Minglin; Ding, Min
Abstract: Objective: To identify possible biomarkers for the clinical grading of intrahepatic cholestasis of pregnancy (ICP) through serum bile acid (SBA) profiling in women with ICP. Methods: Serum samples were collected in the last trimester of pregnancy from 33 women with severe ICP, 28 women with mild ICP, and 35 women with a normal pregnancy. The SBA levels were determined by high‐performance liquid chromatography–tandem mass spectrometry. Results: Patients with severe ICP had significantly higher serum levels of taurochenodeoxycholic acid, tauroursodeoxycholic acid, glycocholic acid (GCA), taurocholic acid (TCA), and glycochenodeoxycholic acid than women with mild ICP or a normal pregnancy. Primary bile acid species, in particular TCA and GCA, were the main bile acids detected and their levels were significantly higher in the severe ICP group than in the other 2 groups. Conclusion: There is an obvious difference in the SBA profiles of women with severe ICP and those with mild ICP, indicating that primary bile acids may be useful biomarkers for the clinical grading of ICP. Implementation of primary bile acid testing in clinical practice may help clinicians to determine the appropriate management strategy for patients with ICP.